Accents, group identity, and trust behaviors : evidence from Singapore - Batsaikhan, Mongoljin (2022)
We study discrimination on the basis of national origin in Singapore by exploring how the group identity discernible in a speaker's accent affects trust. In the trust game, Singaporean Chinese (SGC) senders were asked to listen to audio clips in which responders with either an SGC or a Mainland Chinese (MLC) accent read a two-sentence script before the senders decided how much money to send. We also used the strategy method to elicit the senders' beliefs about the trustworthiness of responders with an MLC accent versus those with an SGC accent. Contrary to our expectations and the common perception in Singapore, we found that Singaporean senders tended to place more trust in responders with an MLC accent than in responders with an SGC accent. We explain this difference on the basis of the Singaporean senders' beliefs about trustworthiness: they believed that people with an MLC accent would return more money to senders than would the in-group Singaporean counterparts. To bolster our findings, we confirmed in a separate experiment that the difference in response to the accents was not due to the speech rate or vocal pitch.